WORKSHOP DIGITAL MARKETING DAN PENYUSUNAN LAPORAN KEUANGAN BAGI SISWA SMKN 51 JAKARTA - Mila Indriastuti; Deni Adha Akbari; Atsna Virayani Yusriy Widarey; Galang Maulana; Afdila Munawati; Piedra Volada Maynard Chassman; Anisa Dwi Fahrini (Jurnal Abdi Mandala, 2022)
In facts, two thirds of Gen-Z or millennials in Asia Pacific have a dream of becoming an entrepreneur. Therefore, the focus of the world of education today is to provide skills for the younger generation to become entrepreneurs, especially for vocational high schools. Digital marketing skills and the preparation of financial reports are the keys to success in winning business competition. Therefore, the community service is focused on providing digital marketing workshops and preparing financial reports both manually and digitally. The object is students majoring in accounting at SMKN 51 Jakarta. The results of the workshop conducted by the PKM 27 Uhamka team proved to have a significant impact on students' abilities in entrepreneurship using digital marketing technology and preparing financial reports. There was an increase in the score of more than 80% in the post-test carried out by SMKN 51 Jakarta students.